Klotho Protein: A Multifaceted Guardian of Healthy Aging and Its Therapeutic Potential - Shen J; Bin W; Lin X; Lai Y; Lin X; Guan T; Liu H (International Journal of Nanomedicine)
Jianlin Shen,1,2,* Wenying Bin,3,* Xiaoning Lin,2,* Yue Lai,4 Xuan Lin,5 Taiyuan Guan,6,7 Huan Liu6,7 1Central Laboratory, Affiliated Hospital of Putian University, Putian, Fujian, 351100, People’s Republic of China; 2Department of Orthopedics, Affiliated Hospital of Putian University, Putian, Fujian, 351100, People’s Republic of China; 3Collage of Integrated Traditional Chinese and Western Medicine, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 4The First Clinical Medical School, Guangdong Medical University, Zhanjiang, Guangdong, 524002, People’s Republic of China; 5Department of Environmental and Biological Engineering, Putian University, Putian, Fujian, 351100, People’s Republic of China; 6Department of Orthopedics, The Affiliated Traditional Chinese Medicine Hospital, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 7Orthopaedic Research Center and Key Laboratory, The Affiliated Traditional Chinese Medicine Hospital, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Taiyuan Guan, Email guanty@swmu.edu.cn Huan Liu, Email 20016040@163.comAbstract: The Klotho protein, encoded by the KL gene, has garnered significant attention as a pivotal biomolecule in the field of aging research. Its expression levels are closely correlated with both lifespan and overall health status, exerting influence over critical physiological processes such as metabolic homeostasis, oxidative stress response, and inflammation modulation. This review aims to systematically examine the multifaceted roles of Klotho within the context of aging and its implications for various age-associated disorders. We highlight the emerging evidence suggesting that Klotho may serve as a key regulator in age-related pathologies, including cardiovascular diseases, neurodegenerative disorders, and metabolic syndromes. Furthermore, we explore the potential of Klotho as a therapeutic target, positing that interventions aimed at enhancing Klotho activity could offer novel strategies for alleviating the health burdens experienced by the aging population.Keywords: Klotho, aging, oxidative stress, inflammation, population aging